Preliminary phytochemical screening and Bioactivity of selected Indian Medicinal plants - AG Devi Prasad,; Shyma TB,; Deepa Shree CL,; Shubha Gopal,; Komal Kumar J, (International Journal of Phytomedicine, 2013)
The methanolic crude extracts of Chonemorpha fragrans (Moon), Chilocarpus malabaricus Bedd Madhuka longifolia (Koenig) J.F.Macbr, Pittosporum neelgherrense Wightt, Raphidophora pertusa (Roxb.) Schott, Fagraea ceilanica Thunb and Rauvolfia tetraphylla L. were screened for the presence of phytoconstituents and their ability to possess antimicrobial and free radical scavenging ability using Chloramphenicol, The methanolic crude extracts of Chonemorpha fragrans (Moon) Alston, Chilocarpus malabaricus Bedd., Madhuka longifolia (Koenig) J.F.Macbr., Pittosporum neelgherrense Wightt., Raphidophora pertusa (Roxb.) Schott., Fagraea ceilanica Thunb., and Rauvolfia tetraphylla L., were screened for the presence of phyto-constituents and their ability to possess antimicrobial and free radical scavenging ability using chloramphenicol, cephoperazone and ascorbic acid as respective standards. Antimicrobial activity was evaluated by Kirby-Bauer disc diffusion method and free radical scavenging activity was evaluated using 1,1-diphenyl-2-picryl hydrazyl (DPPH) free radical and reducing power assay. Pittosporum neelgherrense showed better overall antimicrobial activity and Madhuka longifolia proved better antioxidant ability possessing low IC50 valueof30 µg/ml compared to the other selected medicinal plants. The highest total phenol content was found to be in Chonemorpha fragrans with the value 88±0.121mg/g. The present study reveals that the selected plants serve as a source of antimicrobial and antioxidant drugs in future and thus, can find applications in food and pharmaceutical industries.